Navigating racialized tourism spaces: Apartheid South Africa’s ‘Green Books’ - Rogerson, Christian M. (Bulletin of Geography. Socio-economic Series, 2025)
Racism and racial discrimination in tourism are attracting growing interest. the aim is to contribute to an emergent historical geographical scholarship on racism and racial discrimination in tourism. The greatest progress in exploring the historical bases and legacies of racism in tourism surrounds the Jim Crow era of segregation in the United States which has generated a growing literature. This study is novel as it examines the case of apartheid South Africa. The research represents a contribution to the sparse international literature from destinations outside of the United States concerning the geographical impress of racial discrimination in tourism and of how the racialized populations both countered and navigated a discriminatory landscape of exclusion. It is argued that guidebooks produced in the 1960s by the South African Institute of Race Relations served similar purposes to the well-documented ‘Green Books’ in the USA.